Prospective study of TACE combined with sorafenib vs TACE combined with 125I seed implantation in the treatment of hepatocellular carcinoma with portal vein tumor thrombus and arterioportal fistulas - Zhao, Xiao-Hui; Yuan, Hang; Xia, Wei-Li; Zhang, Li-Lin; Li, Zhen; Cao, Guang-Shao; Li, Hai-Liang; Fan, Wei-Jun; Li, Hong-Le; Guo, Chen-Yang; Yao, Quan-Jun; Zhu, Wen-Bo; et al. (Frontiers in Oncology, 2022)
Abstract: Purpose: To compare the efficacy of TACE combined with sorafenib and TACE combined with 125I seed implantation in the treatment of hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT) combined with arterioportal fistulas (APFs), and discuss the efficacy and safety of TACE combined with 125I seed implantation. Patients and methods: Between January 2017 and December 2018, the clinical data of patients with HCC complicated with PVTT and APFs who were admitted to the Affiliated Cancer Hospital of Zhengzhou University, First Affiliated Hospital of Zhengzhou University, and Henan Provincial People's Hospital were prospectively collected. The patients were divided into the TACE+sorafenib (TACE-S) group based on their treatment willingness. There were 26 and 32 patients in the TACE-S and TACE-125I groups, respectively. Both groups of patients underwent APFs occlusion during TACE therapy. The embolization effect of APFs was observed and recorded in the two groups, the efficacy of intrahepatic lesions and PVTT was evaluated, and the effects of different treatment methods on the efficacy were analysed. Results: All patients completed the 3 months follow-up. The improvement rates of APFs in TACE-S and TACE-125I groups were 30.77% (8/26) and 68.75% (22/32), respectively, and difference was statistically significant (χ2=8.287, P=0.004). The median survival time of TACE-S and TACE-125I groups was 8.00 months and 12.8 months, respectively (χ2=7.106, P=0.008). Multivariate analysis showed that the PVTT subtype (IIa/IIb) and treatment method (TACE-S or TACE-125I) were independent factors affecting the recanalization of APFs in patients (P<0.05). Conclusion: For patients with HCC with PVTT and APFs, TACE combined with 125I seed implantation can effectively treat portal vein tumor thrombus, thereby reducing the recanalization of APFs and prolonging the survival time of patients.